2010
DOI: 10.1007/s12630-010-9391-4
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of undiagnosed diabetes in non-cardiac surgery patients, an observational study

Abstract: Purpose Given that preoperative hyperglycemia is associated with poor outcomes and many non-diabetic patients have high plasma glucose (PG) levels, the purpose of our study was to estimate the prevalence of undiagnosed diabetes among non-cardiac surgery patients and to identify predictors of hyperglycemia in non-diabetics. MethodsWe included all non-cardiac surgery patients with complete records in the Clinical Database of the Anesthesiology Institute at the Cleveland Clinic during January 2007 to April 2009, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 20 publications
(24 reference statements)
1
20
0
Order By: Relevance
“…13 14 In an earlier study, we showed that 21% of noncardiac surgery patients without a diagnosis of diabetes are hyperglycaemic and more than half of those have undiagnosed diabetes. 15 Similar findings have been also reported by Hatzakorzian and colleagues. 16 While previously fasting glucose concentrations were used to diagnose diabetes, 14 more recently, HbA1c has been advocated to be used as a screening test to diagnose diabetes.…”
Section: Adjusted Incidencesupporting
confidence: 85%
“…13 14 In an earlier study, we showed that 21% of noncardiac surgery patients without a diagnosis of diabetes are hyperglycaemic and more than half of those have undiagnosed diabetes. 15 Similar findings have been also reported by Hatzakorzian and colleagues. 16 While previously fasting glucose concentrations were used to diagnose diabetes, 14 more recently, HbA1c has been advocated to be used as a screening test to diagnose diabetes.…”
Section: Adjusted Incidencesupporting
confidence: 85%
“…In a prospective study in 500 patients presenting for elective procedures, 26% of previously undiagnosed patients showed blood glucose levels in the impaired-fasting glucose or diabetic range. 9,10 Protein catabolism Typical features of protein catabolism are stimulated rates of protein breakdown and amino acid oxidation which lead to a net loss of body protein. [11][12][13] Metabolically healthy patients lose 40-80 g of nitrogen after elective abdominal surgery, equivalent to 1.2-2.4 kg of wet skeletal muscle.…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…Although we took all possible precautions to exclude diabetic patients in this study, some of the patients may still have undiagnosed diabetes because of the high prevalence of diabetes in patients undergoing cardiac surgery. 21 A review of our database revealed that 829 patients (22.6%) had an HbA1c measured within 3 months preoperatively. We excluded patients with an HbA1c greater than 6.5%.…”
Section: Study Limitationsmentioning
confidence: 99%